TRAFFIC VOLUME AND ACCIDENT STUDIES ON NH-22 BETWEEN SOLAN AND SHIMLA, INDIA - Rajiv Ganguly; Ashok Kumar Gupta; Mudit Mishra (European Scientific Journal, ESJ, 2014)
This paper is an attempt to study the basic differences between rigid and flexible pavements based on LCCA, durability, recycling, local preference, and safety features. An observation of the traffic count was conducted at Tuttikandi in Shimla and Chambaghat in Solan and difference in vehicular flow was computed. The process involved making manual count of the vehicles passing by on weekdays and weekends. Vehicle fleet was characterized as cars, buses, trucks and motorcycles. The mean traffic flow throughout the week was computed by considering the average of the number of vehicles observed on weekdays and weekends. The study also involved in identifying the ‗black spots‘ which refers to those stretches on Shimla – Solan highway of NH 22 reported with the most number of accidents. Reconnaissance of these locations was carried out to identify the various causes for these accidents. Further, sample of materials used for construction of the highway was collected from these stretches and material testing was carried out. We calculate the SSD and OSD at the regions of ‗black spots‘ and based upon those results suggest suitable remedial measures to prevent such accidents in future including installing various road furniture like convex mirrors, fluorescent sign boards, light poles.